2008
DOI: 10.1002/aic.11516
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of the gas–liquid flow in a stirred tank

Abstract: in Wiley InterScience (www.interscience.wiley.com).Both the large eddy simulation (LES) technique and the k-e turbulent model were used to simulate the gas-liquid turbulent flow in a stirred tank driven by a Rushton impeller. A Eulerian-Eulerian two-fluid model for gas-liquid two-phase flow was developed using the large eddy simulation for both gas and liquid phases. The relative movement of the rotating impeller to the static baffles was accounted for through the improved inner-outer iterative algorithm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…Montante et al (2007Montante et al ( , 2008) solved a population balance equation (PBE) with breakup and coalescence models to predict the local bubble size distribution (BSD). Zhang et al (2008) employed an inner-outer iterative algorithm to model the fluid motion induced by the impeller blades. They concluded that large eddy simulation (LES) provided a greater accuracy than the standard k-e model for the prediction of the mean liquid flow field and the gas holdup.…”
Section: Introductionmentioning
confidence: 99%
“…Montante et al (2007Montante et al ( , 2008) solved a population balance equation (PBE) with breakup and coalescence models to predict the local bubble size distribution (BSD). Zhang et al (2008) employed an inner-outer iterative algorithm to model the fluid motion induced by the impeller blades. They concluded that large eddy simulation (LES) provided a greater accuracy than the standard k-e model for the prediction of the mean liquid flow field and the gas holdup.…”
Section: Introductionmentioning
confidence: 99%
“…The Eulerian-Eulerian large eddy simulation (LES) turbulence model has shown significant promise in unearthing flow details in multiphase systems like, in gas-liquid multiphase systems (Deen et al, 2001;Dhotre et al, 2008;Tabib et al, 2008;Zhang et al, 2008;Niceno et al, 2008), in liquid-solid particle systems involving stirred vessel (Derksen, 2006), in fluidized bed (Chiesa et al, 2005) and particle laden flow (Riber et al, 2009). Though there is one drawback while applying the Eulerian-Eulerian LES, that is in-order to maintain the consistency of the assumption of interpenetrating continua, the largest interface details should be smaller than the grid size, which means that the cell size must be larger than the particle size.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CFD may be used for the design and optimization of stirred tanks either for solid-liquid mixing (Fig. 8) or gas-liquid mixing [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…This type is more appropriate for dispersion of gas in liquid [31,32]. In this case, LES are conducted to study the path and shape of single air bubbles rising freely in water.…”
Section: Roughly 4 · 10mentioning
confidence: 99%